Quo Vadis Pilkada Indonesia - Wira Atma Hajri (UIR Law Review)
Based on Article 18 Paragraph (4) of the 1945 Constitution, the election of regional heads is a matter of open legal policy, so that direct or indirect election is the same democratic election. Therefore, this does not need to be disputed. The thing that needs to be addressed is why the election of regional heads so far resulted in many heads of regions involved in corruption cases.